BENTALL PROCEDURE IN THE TREATMENT OF AORTIC DISSECTION (AD) – CURRENT STATE OF KNOWLEDGE AND LITERATURE REVIEW - Furgoł, Tomasz; Gigoń, Konrad; Jureczko, Joanna; Kasza, Robert; Ratajczak, Maksymilian; Smreczak, Maciej; Jezierzański, Marcin; Miciak, Michał; Mularska, Dominika (International Journal of Innovative Technologies in Social Science, 2026)
Background: Aortic dissection (AD) is a rare but life-threatening condition caused by damage to the aortic wall, leading to abnormal blood flow and severe complications such as tissue perfusion disorders, potential rupture, and fatal hemorrhage. Diagnosis is primarily based on imaging studies, and in cases of acute type A aortic dissection (TAAD), urgent cardiac surgical intervention is required. Treatment generally involves replacing the affected segment of the aorta, sometimes in conjunction with the aortic valve. A common surgical approach is the Bentall procedure. Objectives: This review examines the effectiveness, benefits, and associated complications with the Bentall surgery in AD therapy, and a comparison between valve sparing and aortic replacement methods. Methods: A comprehensive search was conducted in online databases. The analyzed publications included original research articles, meta-analyses, review papers, clinical guidelines, seminar articles, comparative studies, and retrospective case series. Results: Both mechanical and biological composite grafts are viable options, with no definitive evidence favoring one over the other in terms of major complications or long-term survival; however, mechanical prostheses may offer a slight advantage in younger patients. In select emergency cases, limited repair without root replacement may yield favorable short-term outcomes, though current data are insufficient to draw firm conclusions. Emerging techniques, such as the ENDO-Bentall, represent promising innovations that may enhance procedural safety and expand treatment options. Conclusions: The Bentall procedure remains the cornerstone in the surgical management of acute type A aortic dissection, particularly when the aortic root or valve is compromised.